Pengaruh Pendapatan Asli Daerah (PAD) dan SiLPA Terhadap Indeks Pembangunan Manusia (IPM) melalui Belanja Modal di Provinsi Bali - Teguh Pratama, I Gusti Ngurah Putu; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 11. Nopember 2017(pp.2103-2351), 2017)
ABSTRACT This study aims to determine the effect of district own source revenue and financing surplus (SiLPA) on the Human Development Index ( HDI ) through Capital Expenditure in Bali Province. This study covers 9 districts / cities in the province of Bali. The purpose of this study is to determine the effect of local revenue and SiLPA on human development index through capital expenditure. The analysis technique used is path analysis. The result of research indicates that regional income and SiLPA have positive and significant influence to human development index through Capital Expenditure with PAD value toward Capital Expenditure is 5,343 sig 0,00. SiLPA to Capital Expenditure is 2,916 with sig 0.004. PAD to HDI of 4,616 sig 0,00, SiLPA to HDI of 2,009 sig 0,048 and Capital Expenditure to HDI 2,234 with sig 0,039. Keywords: district own source revenue, SiLPA, Human Development Indeks (HDI), Capital Expenditure